Factors Affect the Disclosure of Islamic Social Reporting at Sharia Commercial Banks - Fauziah, Hana; Rahmawati, Yuke (SAN Scientific, 2023)
Today the credit of the sharia bank is based on its social activity, which impacts its economic activities. The study analyzes factors that affect Islamic social inequality in the sharia bank at IDX. The research uses the secondary data of the annual report with a sample of 4 buses going public in 2018-2020. A non-sampling sample with a saturated sample type uses the sample retrieval technique. The data analysis method used is the regression test panel using the Eviews software 10. The results of this study indicate that good corporate governance and exposure variables do not significantly affect Islamic Social Reporting (ISR), with variable corporate size affecting Islamic Social Reporting (ISR). In comparison, there is simultaneously no influence between affirmative governance variables, exposure media, and the firm's size On Islamic Social Reporting (ISR). The implications of this research are expected to be able to provide theoretical contributions related to the disclosure of Islamic social responsibility. They are useful in providing input for policymakers and regulators on the Indonesia Stock Exchange.